2018
DOI: 10.1097/shk.0000000000001064
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Aromatic Metabolites in the Pathogenesis of Septic Shock

Abstract: AMM are involved in the pathogenesis of septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 31 publications
2
29
0
4
Order By: Relevance
“…Furthermore, one study of patients with community acquired pneumonia admitted to the ICU, reported that NT‐proBNP was significantly higher in patients with septic shock, compared to patients without septic shock. While patients with non‐infectious shock were excluded from the study, the authors did not clarify whether patients without septic shock suffered from sepsis or severe sepsis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, one study of patients with community acquired pneumonia admitted to the ICU, reported that NT‐proBNP was significantly higher in patients with septic shock, compared to patients without septic shock. While patients with non‐infectious shock were excluded from the study, the authors did not clarify whether patients without septic shock suffered from sepsis or severe sepsis …”
Section: Resultsmentioning
confidence: 99%
“…While patients with non-infectious shock were excluded from the study, the authors did not clarify whether patients without septic shock suffered from sepsis or severe sepsis. 58 In contrast to these results, a study by Hämäläinen et al, conducted in patients with neutropenic fever, demonstrated that serial NT-proBNP measurements could not predict the development of severe sepsis. 49…”
Section: Ability Of Brain Natriuretic Peptides To Distinguish Betwementioning
confidence: 89%
“…It was shown that in vitro some sepsis-associated AMM in clinically significant concentrations can inhibit the phagocytic activity of neutrophils [17]; cause mitochondrial dysfunction [18]; influence on platelet aggregation [19]; reduce tyrosine hydroxylase activity, thus limiting the synthesis of catecholamines; and participate in the pathogenesis of septic shock [20]. Numerous data obtained in vitro allow us to hypothesize that AMM acts as signaling molecules ( Figure 3).…”
Section: The Gut Microbial Metabolites In the Pathogenesis Of Sepsismentioning
confidence: 99%
“…It is impossible to exclude the presence of common signaling pathways, cell receptors, transmembrane transporters, and other mechanisms of humans and bacteria, as well as the direct participation of microbial metabolites in the pathogenesis of sepsis. Thus, today, we should not confine ourselves to studying eukaryotic cells while searching for new molecular mechanisms of sepsis-associated organ failure and septic shock [20]. We should consider and simulate experimental changes in the internal environment of a person that occur with a radical "restructuring" of the microbiome in seriously ill patients.…”
Section: The Gut Microbial Metabolites In the Pathogenesis Of Sepsismentioning
confidence: 99%
“…Важное значение играют ароматические микробные метаболиты (АММ) фенольной природы: например, ассоциированные с развитием септического шока и летальным исходом -пара-гидроксифенилуксусная кислота (п-ГФУК) [27,28], фенилмолочная (ФМК) и пара-гидроксифенилмолочная (п-ГФМК) кислоты [29].…”
Section: перспективы в нейрореабилитологииunclassified